The Effect of Private Management of Public Schools on Student Achievement in Bogotá, Colombia (2015)
During the last 15 years, the public school system in Bogotá, Colombia has maintained a concession system in which 25 schools are managed privately with exemptions to many of the rules required in the traditional schools -- This study uses the propensity score matching technique to examine whether students in the privately-managed schools have better scores on the Saber 11° examinations taken upon completion of secondary school -- The results for 251 schools indicates that students with comparable socioeconomic characteristics score considerably better on these tests in the privately-managed schools than in the traditional public schools -- Thus, there is evidence that the privately-managed public schools are a cost-effective alternative to the traditional public school